Religious Authority Fails to Mobilize Voters in Indonesian Local Politics - Raegen Harahap (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2026)
Religious authority has long been considered an influential factor in shaping electoral behavior in Indonesia. However, the effectiveness of religious endorsements in contemporary local elections remains contested. This study examines the failure of religious authority to mobilize voter support in the 2024 Kampar Regency Election, despite the endorsement of Ustadz Abdul Somad (UAS), one of Indonesia’s most prominent Islamic preachers. Previous studies have primarily highlighted the success of religious leaders in influencing electoral outcomes through patronage networks, clientelistic relationships, and religious legitimacy. Limited attention, however, has been paid to cases in which religious authority fails to generate electoral gains. To address this gap, this research employs a mixed-methods approach that combines a survey of 200 respondents with semi-structured interviews with younger and older voter groups in Kampar Regency, Riau Province. Quantitative data were analyzed descriptively, while qualitative data were examined using thematic analysis. The findings reveal that although UAS enjoys widespread recognition and strong religious credibility, his endorsement had little influence on voting decisions. Instead, regional identity, candidate track records, ethnic proximity, and socio-political connections emerged as more decisive factors. This study contributes to the literature by demonstrating the limitations of symbolic religious legitimacy in electoral mobilization and highlighting the importance of embedded social and political networks in shaping voter preferences.